Mengeksplorasi Legitimasi atau Adopsi NFT (Non-Fungible Token) pada Pelaku Ekonomi di Indonesia dengan Menggunakan Metode ZMET (Zaltman Metaphor Elicitation Technique) - Ari Okta Viyani; Wahyu Adi Mudiparwanto; Syah Ammar Brawijaya Siraj (CV. Strata Persada Academia, 2023)
Non-fungible token (NFT) is a new type of blockchain-based token that is unique and cannot be divided. The existence of NFT technology provides benefits for the realization of a digital economy in the future. However, not much research has been done on this technology. Apart from that, the adoption and level of legitimacy of NFT technology for economic actors in Indonesia is also still very limited. Therefore, the role of adoption and legitimacy for economic actors in Indonesia needs to be increased, considering the many benefits of this technology for the realization of a digital economy in the future. To be able to increase the level of adoption and legitimacy for economic actors in Indonesia, the first thing that needs to be done is to know the basic reasons someone wants to accept (legitimize) and then use (adopt) the technology. If the basic reasons are known, the government can implement policies that are able to encourage higher technology adoption. This research uses the ZMET (Zaltman Metaphor Elicitation Technique) technique. This method is able to reveal a person's subconscious thoughts, which are sometimes hidden during interviews.